Traditional furniture. The effects from the introduction of new methods of materials / Alfian Gunawi - Gunawi, Alfian (Faculty of Architechture , Planning & Surveying, 1992)
The study will investigate the positive and negative effect of the modernisation process on traditional design of furniture. The study will also cover these aspects in briefs: traditional furniture design concepts, evolution, methods of construction and materials used. And modern furniture design in relation to our local context in term of construction and materials.